EFFECTIVENESS OF CONTINUOUS AND COMPREHENSIVE EVALUATION (CCE) ON THE DEVELOPMENT OF HIGHER MENTAL ABILITIES IN SCIENCE STUDENTS - Rizvi, Nusrat (SCHOOL SCIENCE, 2014)
Since independence till today many reasearches as well as innovative steps have been tried by secondary educational boards of India, which are mainly emphasising upon the all-round development of the students. In this context, Central Board of Secondary Education(CBSE) applied Continuous and Comprehensive Evaluation(CCE) system in Class X (2010-2011). In the present research paper, the researcher wants to see the effectiveness of CCE on the development of higher mental abilities i.e. application, analysis, synthesis and evaluation in science students. For this purpose, a comparative study was made between the science students of Class XI from the CBSE board (who faced the CCE pattern in Class X) and the science students of the same class from UP board (who did not face the CCE pattern in Class X) in 2010-2011. For the present study, hundered students from CBSE board and 100 from UP Board of Bulandshahr district were selected through stratified random sampling technique. A test of higher mental abilities developed by the investigator on the basis of a standardised test developed by Dr D.N. Sansanwal and Dr Anuradha Joshi (1989) was administered on the students. Findings of the study indicate no significant difference in the development of higher mental abilities of science students of both the boards i.e., the CBSE Board and UP Board. The findings support the reconsideration of the applied part of CCE system followed by the CBSE Board.